Commercial Justice Of Intellectual Property Rights From The Perspective Of Ushul Fiqh : Analysis Of Licensing, Trade Secrets, Industrial Designs, And Integrated Circuit Layout Designs (Icld) As The Implementation Of Hifz Al-Mal - Rina Bahren (Islamic Circle, 2026)
Intellectual Property Rights (IPR) have become an essential component of the modern knowledge-based economy. Through licensing, trade secrets, industrial designs, and integrated circuit layout designs, intellectual creations generate economic value and contribute to technological development. Nevertheless, commercialization practices often raise concerns regarding monopoly, unequal bargaining positions, and unequal access to innovation. This study aims to analyze the commercialization of intellectual property rights from the perspective of Islamic legal theory (ushul fiqh) and maqasid al-shariah. This research employs normative legal research with a qualitative approach through literature review and conceptual analysis. The findings indicate that intellectual property rights are consistent with the objective of hifz al-mal (protection of wealth) within maqasid al-shariah. However, commercialization must be guided by the principles of justice ('adl), prevention of harm (la darar wa la dirar), public welfare (maslahah), and equitable distribution of benefits. The study concludes that intellectual property protection is permissible in Islamic law as long as it does not create injustice, exploitation, or excessive monopoly.